Study on the Fluorescence Spectra Characteristics of Vinegar-Water Solutions - Dan Li; Xuan Wang; Caiqin Han (Journal of Spectroscopy)
Fluorescence spectra and polarization spectra of vinegar-water solutions with different concentration of CH3COOH have been studied. The characteristics and mechanism of fluorescence spectra are discussed, and polarization degree is calculated. Vinegar-water solutions are excited by ultraviolet (UV) light at 380 nm. The characteristic fluorescence peaks of the solution were identified at 445 nm and 470 nm. The type of emission fluorescence is π⁎→n. With the increasing concentration of CH3COOH/pH value, the peak intensity is enhanced first, and then fluorescence quenching occurs. The polarization degree confirms the molecular orientation of different sample solutions. This research provides theoretical and experimental basis for the physical/chemical properties and quality of vinegar detection by florescence spectroscopy.